SPECIAL CHARACTERISTICS OF THE EDUCATION PROCESS OF ALTERNATIVE SCHOOLCHILDREN IN THE USA - Inna Stanislavovna Bessarabova; Anton Valerievich Kobzar; Irina Sergeevna Nikitina (Sovremennye Issledovaniâ Socialʹnyh Problem, 2015)
The urgency of the topic is stipulated by the importance of the problem of education of the schoolchildren who have other (alternative) physical or mental development and who belong to a separate cultural group with its own features, possibilities and needs in education. The purpose of the research is to reveal the essential parts of the inclusive educational environment in the approaches of American scholars. The problem is studied in the context of multicultural education. The results of the research showed that the formation of the inclusive educational environment should be based on the principles of multicultural education: anti-racist character of education, which rejects any forms of discrimination of schoolchildren; orientation to the achievement of social justness; liberal character (education helps a person to overcome self-oppression and lack of confidence in one’s efforts); transmission character (a person transmits knowledge and skills from school community to society); transactional character (inclusive educational environment provides the opportunity of mutual transaction of the representatives of two different cultures – alternative children and traditional children); transformational cha-racter (an alternative child is transformed from the passive object of the life care of the family into the ultimate self-sufficient subject who is able to take part in the life of the society). Practical implications of the results. The results of the research are applicable in the process of working out of the new technologies, methods and approaches in education to create inclusive educational environment in educational institution and in the process of the development of multicultural competence as an essential personal quality of a modern professional.